Resilience factors and mechanisms in the coal power supply chain: A quantitative analysis using fuzzy DEMATEL, ISM, and ANP methods - Yingchen Wang; Mingkang Li; Linlin Sun; Jiaqing Liu; Yiran Wang (PLoS ONE, 2025)
Under the influence of global energy market fluctuations, policy changes, and natural disasters, the coal power supply chain faces significant risks. However, existing research on supply chain resilience management, particularly regarding the identification and quantitative analysis of resilience factors in the coal power supply chain, remains insufficient. Therefore, this study aims to identify the key factors influencing the resilience of the coal power supply chain and analyze the mechanisms of interaction between these factors. This study first conducted a literature review to identify 20 factors classified into three dimensions: adaptive capacity, restorative capacity, and absorptive capacity. Secondly, an innovative approach integrating fuzzy DEMATEL, ISM, and ANP was introduced to systematically identify the key influencing factors of coal power supply chain resilience and analyze their mechanisms. The results reveal that electricity demand forecasting capability, government intervention and coordination capacity, and technological level of the coal industry are the primary causal factors affecting supply chain resilience, playing critical roles in ensuring supply chain stability and adaptability. Additionally, factors such as risk prevention and maintenance level and information transmission efficiency also serve as important supporting elements. This research constructs a cause-degree-centeredness diagram and a hierarchical model for coal power supply chain resilience, providing theoretical support and practical recommendations for optimizing the supply chain structure and enhancing the capacity to cope with uncertainties in the coal power industry.